"I forget who I am while I remember who I was so I can perform who I am": memory, embodied practice, and thing-power in theater-making. Issue 1 (2nd January 2022) - Dennis, Rea; Hunter, Kate; Miranda, Magda
ABSTRACT: The theater affords us a way to think. It holds, inflects, and problematizes memory, and opens an alternate space within which to interrogate memory as an individual experience and a shared collective phenomenon. This essay interrogates memory as central to the theme, content and form of the theater-making process. Examining the question "How can performance facilitate memory and how can memory facilitate performance?" (Shaughnessy, Nicola. Applying Performance: Live Art, Socially Engaged Theatre and Affective Practice. London: Palgrave, 2012), we analyse the performer's experience in relation to Antonio Damasio's conceptualization of somatic markers and Jane Bennett's notion of "thing-power" to consider the ways in which the body in theater honors the plurality of memory.